Metrics, mapping, and modelling for masterful management in higher education - Glynn, Graham (Emerald Publishing Limited, 2025)
Higher Education Institutions (HEIs) are under immense pressure to become more efficient, reduce fees, and lower student debt, all while maintaining an expected high standard of academic excellence. This pressure creates the sense that HEIs must evolve to become more 'business-like' but fails to consider the unique expertise of their faculty and their role in shared governance. In combination with the high turnover rates of senior administrators this creates a culture which conflicts with and resists the adoption of these business-like practices. However, a business approach that integrates transparency and stakeholder engagement means that the two approaches are not necessarily wholly incompatible. Graham Glynn explores such an environment, using concept map-based institutional modelling to empower transparent, knowledge-informed, and strategic management to improve stakeholder engagement and shared governance in the educational sphere. Combining theoretical analysis with practical implementation guides and management tools, uniquely accompanied by the Sentient Knowledge Map (SKM), a templated model of an HEI which offers an overarching view to enable readers to appraise the complex, intertwined operations of an institution in one place. In addition, the access to the companion e-learning community at HelloCommunity.net provides a platform where administrators can go further and share best practises, find mentors, and explore global professional development opportunities. More than just a book, Metrics, Mapping, and Modelling for Masterful Management in Higher Education is a collaborative initiative to enrich management and communication within HEIs across the globe, reduce reduplication, and create an environment for shared knowledge and resources to benefit institutions everywhere.
Keywords: Universities and colleges -- Business management.; Education -- Schools -- Levels -- Higher.; Higher education, tertiary education.; elektronické knihy; electronic books